IDENTIFIKASI KELAYAKAN JEMBATAN BATANGHARI II KOTA JAMBI MENGGUNAKAN MIKROTREMOR DENGAN METODE HORIZONTAL TO VERTICAL SPECTRAL RATIO (HVSR) - Oky Dwi Syaputra; Faizar Farid; Samsidar Samsidar; Linda Handayani (Komunikasi Fisika Indonesia, 2019)
The feasibility study of Batanghari II Bridge with the value of natural frequency of Bridge using microtremor has been done. The purpose of this research is to know the bridge's natural frequency value using Horizontal to Vertical Spectral Ratio (HVSR) method and to know the relative damage to Bridge. In this study Bridge as an object because, Bridge is an alternative way that connects one place with another place separated by a river or ditch which is often used by society for activity. To get the bridge's natural frequency value using Microtremor sensor which is directly placed bridged with geopsy software to process its data and using HVSR method. The result of this research is the natural bridge frequency value of 7.40441 Hz. To determine the feasibility of the bridge compared with the standard value of the bridge frequency of 7,675 Hz and stated the state of the Batanghari II bridge is still intact from the structural and the natural frequency value of the soil on the bridge buffer of 12.7489 Hz and 13.6343 Hz that the soil type is older soil. Can be said the foundation of the bridge last long.